2022
DOI: 10.1186/s13287-022-02702-9
|View full text |Cite
|
Sign up to set email alerts
|

The cannabinoid receptor I (CB1) enhanced the osteogenic differentiation of BMSCs by rescue impaired mitochondrial metabolism function under inflammatory condition

Abstract: Background Periodontitis is a chronic infectious disease leading to bone resorption and periodontal tissue disruption under inflammatory stimulation. The osteogenic differentiation ability of mesenchymal stem cells (MSCs) is impaired under the inflammatory environment, which limits the effect of treatment. The cannabinoid receptor I (CB1) is the main effector of the endogenous cannabinoid system (ECS), and our previous study verified that CB1 could enhance the osteo/dentinogenic differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…These data confirm the involvement of CB1 and CB2, and of the epithelium associated with periodontal inflammation, in line with the results of previous research 22,24 . Studies observed that cannabinoid receptors seem to play a role in the promotion of periodontal tissue healing by the improvement of fibroblast adhesion and migration, and by enhancing the osteo/dentinogenic differentiation of periodontal ligament stem cells even during tissue inflammation 17,24,31,32 . According to our results, inflammation does not seem to impact predominantly on one of the two receptors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These data confirm the involvement of CB1 and CB2, and of the epithelium associated with periodontal inflammation, in line with the results of previous research 22,24 . Studies observed that cannabinoid receptors seem to play a role in the promotion of periodontal tissue healing by the improvement of fibroblast adhesion and migration, and by enhancing the osteo/dentinogenic differentiation of periodontal ligament stem cells even during tissue inflammation 17,24,31,32 . According to our results, inflammation does not seem to impact predominantly on one of the two receptors.…”
Section: Discussionsupporting
confidence: 93%
“…22,24 Studies observed that cannabinoid receptors seem to play a role in the promotion of periodontal tissue healing by the improvement of fibroblast adhesion and migration, and by enhancing the osteo/dentinogenic differentiation of periodontal ligament stem cells even during tissue inflammation. 17,24,31,32 According to our results, inflammation does not seem to impact predominantly on one of the two receptors. Literature reports that CB1 receptors are mainly located in the central and peripheric nervous system, but it also has been found partially expressed in periodontal tissue as well as testis, retina, bone, adipocytes, heart, lung, prostate, spleen, uterus and ovaries.…”
Section: Discussionsupporting
confidence: 55%
“…However, the regulatory mechanism of MSCs in an inflammatory microenvironment remains controversial. Some studies have found that the inflammatory cytokines IFN-γ, TNF-α and IL-1β can inhibit the osteogenic differentiation, immunoregulation and proliferation functions of MSCs [ 84 , 85 , 86 ], whereas other studies have shown that low levels of inflammatory stimulation, such as with the stimulation of LPS, the immunomodulatory properties of mBMSCs were increased. Moreover, the expression of collagen I and osteocalcin (OCN) in human PDLSCs were downregulated under Pg-LPS stimulation conditions, and calcium formation was decreased in mBMSCs by LPS at 1 μg/mL [ 87 , 88 , 89 ].…”
Section: Effects Of Host Mesenchymal Stem Cells On Immune Cell Regula...mentioning
confidence: 99%
“…It is reported that the differentiation of MSCs is often accompanied by mitochondrial biogenesis, which is controlled by PGC-1 α and further activates Nrf1, Nrf2 and mtTFA expression in coordination with γ polymerase to promote mtDNA replication. The increased expression of Nrf1 and Nrf2 can increase the mitochondrial biogenesis of hBMSCs, thus enhancing the osteogenic differentiation potential of hBMSCs ( 94 , 95 ). FNDC5-pretreated BMSC-Exos were also shown to have anti-inflammatory effects and promote M2 macrophage polarization through the NF-κB signaling pathway and the Nrf2/HO-1 axis ( 96 ).…”
Section: Nrf2 Is Involved In the Regulation Of Periodontal Diseasementioning
confidence: 99%